Two New Ainsliaea Species (Asteraceae: Pertyoideae) From Southeast China: Based on Morphological Characters and Phylogenetic Evidence - Cheng‐Yuan Zhou; Xiangxiu Su; Chunyi Wei; Liang Ma; Shi‐Pin Chen (Ecology and Evolution)
ABSTRACT Two new species of Ainsliaea (Asteraceae: Pertyoideae), Ainsliaea erectifolia X.X.Su and S.P.Chen and Ainsliaea laxiflora X.X.Su and S.P.Chen, both from Fujian, Southeast China, are described and illustrated here. Morphologically, A. erectifolia is similar to A. simplicissima, but can be distinguished by both surfaces of leaves being glabrous and the capitulum bearing 3 flowers. A. laxiflora is similar to A. polystachya , but differs by its rosette leaves aggregating near the middle part of the stem, the capitulum bearing 3 flowers, the terminal inflorescence rachilla shorter than lateral rachillae, anthers lower than corolla lobes, and style equal to or slightly higher than corolla lobes. Phylogenetic analyses indicated that the two new species were closely related to each other and belong to section Aggregatae. These two species have currently been assessed as Critically Endangered (CR) according to the IUCN guidelines. Furthermore, the complete plastid genomes of these two new species are reported. This study not only introduces two new Ainsliaea species but also provides their plastid genome data, offering valuable genetic resources for understanding the evolutionary history of the genus Ainsliaea.